Inherited Neuromuscular Disorders: Which Role for Serum Biomarkers? - Antonino Lupica; Vincenzo Di Stefano; Andrea Gagliardo; Salvatore Iacono; Antonia Pignolo; Salvatore Ferlisi; Angelo Torrente; Sonia Pagano; Massimo Gangitano; Filippo Brighina (Brain Sciences, 2021)
Inherited neuromuscular disorders (INMD) are a heterogeneous group of rare diseases that involve muscles, motor neurons, peripheral nerves or the neuromuscular junction. Several different lab abnormalities have been linked to INMD: sometimes they are typical of the disorder, but they usually appear to be less specific. Sometimes serum biomarkers can point out abnormalities in presymtomatic or otherwise asymptomatic patients (e.g., carriers). More often a biomarker of INMD is evaluated by multiple clinicians other than expert in NMD before the diagnosis, because of the multisystemic involvement in INMD. The authors performed a literature search on biomarkers in inherited neuromuscular disorders to provide a practical approach to the diagnosis and the correct management of INMD. A considerable number of biomarkers have been reported that support the diagnosis of INMD, but the role of an expert clinician is crucial. Hence, the complete knowledge of such abnormalities can accelerate the diagnostic workup supporting the referral to specialists in neuromuscular disorders.